Hydrophobic alkyl chains substituted to the 8-position of cyclic nucleotides enhance activation of CNG and HCN channels by an intricate enthalpy - entropy compensation. Issue 1 (December 2018) - Otte, Maik; Schweinitz, Andrea; Bonus, Michele; Enke, Uta; Schumann, Christina; Gohlke, Holger; Benndorf, Klaus
Abstract Cyclic nucleotide-gated (CNG) and hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are tetrameric non-specific cation channels in the plasma membrane that are activated by either cAMP or cGMP binding to specific binding domains incorporated in each subunit. Typical apparent affinities of these channels for these cyclic nucleotides range from several hundred nanomolar to tens of micromolar. Here we synthesized and characterized novel cAMP and cGMP derivatives by substituting either hydrophobic alkyl chains or similar-sized more hydrophilic heteroalkyl chains to the 8-position of the purine ring with the aim to obtain full agonists of higher potency. The compounds were tested in homotetrameric CNGA2, heterotetrameric CNGA2:CNGA4:CNGB1b and homotetrameric HCN2 channels. We show that nearly all compounds are full agonists and that longer alkyl chains systematically increase the apparent affinity, at the best more than 30 times. The effects are stronger in CNG than HCN2 channels which, however, are constitutively more sensitive to cAMP. Kinetic analyses reveal that the off-rate is significantly slowed by the hydrophobic alkyl chains. Molecular dynamics simulations and free energy calculations suggest that an intricate enthalpy - entropy compensation underlies the higher apparent affinity of the derivatives with the longer alkyl chains, which is shown to result from a reduced loss of configurational entropy upon binding.